An Engineering Model for Compaction of Sand Under Cyclic Loading - A. Sawicki (Engineering Transactions, 1987)
A model for compaction of saturated sand subjected to cyclic loading is proposed. The model has been formulated in terms of the cyclic stress and strain amplitudes. The first equation describing the model is the compaction law, the second one is the stress -strain relationship between cyclic amplitudes. A correlation of constitutive equations with cyclic loading data is presented. Pore pressure generation under cyclic loading in undrained conditions is evaluated to illustrate predictions of the model.